The Drosophila F-box protein dSkp2 regulates cell proliferation by targeting Dacapo for degradation. - Dui, W.; Wei, B.; He, F.; Lu, W.; Li, C.; Liang, X.; Ma, J.; Jiao, R. (Molecular Biology of the Cell, 2013)
Cell cycle progression is controlled by a complex regulatory network consisting of interacting positive and negative factors. In humans, the positive regulator Skp2, an F-box protein, has been a subject of intense investigation in part because of its oncogenic activity. By contrast, the molecular and developmental functions of its Drosophila homologue, dSkp2, are poorly understood. Here we investigate the role of dSkp2 by focusing on its functional relationship with Dacapo (Dap), the Drosophila homologue of the cyclin-dependent kinase inhibitors p21(cip1)/p27(kip1)/p57(kip2). We show that dSkp2 interacts physically with Dap and has a role in targeting Dap for ubiquitination and proteasome-mediated degradation. We present evidence that dSkp2 regulates cell cycle progression by antagonizing Dap in vivo. dSkp2 knockdown reduces cell density in the wing by prolonging the cell doubling time. In addition, the wing phenotype caused by dSkp2 knockdown resembles that caused by dap overexpression and can be partially suppressed by reducing the gene dose of dap. Our study thus documents a conserved functional relationship between dSkp2 and Dap in their control of cell cycle progression, suggesting the possibility of using Drosophila as a model system to study Skp2-mediated tumorigenesis.